2019
DOI: 10.3390/genes10050384
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymorphisms in RAPGEF6 Gene Associated with Egg-Laying Rate in Chinese Jing Hong Chicken using Genome-Wide SNP Scan

Abstract: The improvement of egg production is of vital importance in the chicken industry to maintain optimum output throughout the laying period. Because of the elongation of the egg-laying cycle, a drop in egg-laying rates in the late laying period has provoked great concern in the poultry industry. In this study, we calculated the egg-laying rate at weeks 61–69 (60 days) of Jing Hong chickens parent generation as the phenotype, and the genotype were detected by the chicken 600K Affymetrix Axiom High Density (HD) Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
(69 reference statements)
0
11
0
2
Order By: Relevance
“…At present, the field of ovulation-related gene research is still in the stage of studying the functions of single genes ( Azmal et al 2019 , Zhou et al 2019 ). For example, a study found that the recombinant Homeobox protein akr ( Akr ) gene reduced the oviposition amount of Dermanyssus gallinae (Acarina: Dermatophagoideae), and the application of recombinant Deg-akr protein produced by the Akr gene to the adult body surface of D. gallinae affected egg-laying behavior, resulting in a 42% reduction in oviposition ( Lima-Barbero et al 2019 ).…”
Section: Genes Related To Oviposition and Hatchingmentioning
confidence: 99%
“…At present, the field of ovulation-related gene research is still in the stage of studying the functions of single genes ( Azmal et al 2019 , Zhou et al 2019 ). For example, a study found that the recombinant Homeobox protein akr ( Akr ) gene reduced the oviposition amount of Dermanyssus gallinae (Acarina: Dermatophagoideae), and the application of recombinant Deg-akr protein produced by the Akr gene to the adult body surface of D. gallinae affected egg-laying behavior, resulting in a 42% reduction in oviposition ( Lima-Barbero et al 2019 ).…”
Section: Genes Related To Oviposition and Hatchingmentioning
confidence: 99%
“…Under the action of multiple lipid transfer proteins, these lipids are assembled into very low density lipoprotein (VLDL) particles that are transported to the follicle [ 18 , 24 ]. For this reason, and coupled with the extension of the laying cycle from the first 72–80 weeks, some breeding companies have even prolonged the laying age to 100 weeks [ 25 , 26 ]. Continuous egg production with a high dietary consumption of carbohydrate can markedly induce adiposity, increasing the risk of FLD, as well AS [ 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association study(GWAS) can provide preliminary results in genetic research on complex traits in animals. Many single nucleotide polymorphism (SNP) loci and qualitative trait loci(QTL) with strong statistical signi cance have been discovered [6][7][8][9]. GWAS has become a powerful tool for studying important economic traits of livestock and poultry and has promoted research on marker-assisted breeding.…”
Section: Introductionmentioning
confidence: 99%